Implementing integrated STEM teaching in design and technology: teachers' knowledge and teaching practices - Razali, Hamidah; Jamaluddin, Rahimah; Kamarudin, Nurzatulshima (Human Resource Management Academic Research Society, 2022)
Malaysia has emphasized the integration of Science, Technology, Engineering, and Mathematics (STEM) in Technical and Vocational Education and Training (TVET) to ensure the supply of manpower in the industry meets the requirements of Digital 4.0. However, teachers’ teaching practices in the classroom were found to be the cause of the declining number of students taking STEM subjects in secondary schools. Teachers’ knowledge is important to ensure an integrated STEM teaching can be implemented effectively. Knowledgeable teachers in STEM discipline will increase confidence to apply integrated STEM in teaching and learning (T&L). This study was conducted to examine the level of teachers’ knowledge and its relationship with STEM teaching practices among Design and Technology teachers. This quantitative study involved 375 Design and Technology teachers from 99 of secondary schools on the East Coast of Malaysia. This quantitative study using stratified random sampling technique to determine the sample. The questionnaire consisting 61 items distributed online via Google Form. Descriptive analysis and Pearson correlation were performed using Statistical Package for Social Science version 26.0. The analysis showed that Design and Technology teachers’ level of knowledge is high with a score of M = 3.20 and SD = 0.35, while the integrated STEM teaching practices are at a moderate level with a score of M = 2.97 and SD = 0.46. Furthermore, knowledge on integrated STEM teaching practices among Design and Technology teachers exhibited a moderate and significant positive relationship with a score of r = 0.356 and p<0.05. The findings indicated that teachers do implement integrated STEM teaching practices but not comprehensively and consistently. They are in the knowledge development phases in understanding the STEM concept and implementing it in the Design and Technology curriculum. Furthermore, STEM teaching has yet to be part of their teaching culture. They require time to adapt STEM teaching into their existing teaching practices. Therefore, teachers need additional support from school administrators, departments, and the Ministry of Education (MOE) to participate in "hands-on" and "minds-on" courses related to STEM T&L. Further research is needed on integrated STEM teaching practices using different approaches involving engineering design process to fill the gap in teaching practices among Design and Technology teachers.